DIGITAL STORYTELLING IN TEACHING WRITING - Umayyah, Wahda Latifah Nur Ikhwani (2017)
The study entitled "Digital Storytelling in Teaching Writing" aimed to investigate the use of digital storytelling in helping junior high school students' in learning writing recount text, students' responses toward the use of digital storytelling, and to find out students' difficulties during writing recount text through digital storytelling. This study used online-based digital storytelling named Zimmertwins. The mixed method-exploratory design was employed to obtain the data. Furthermore, the classroom observation, interview, and questionnaire were chosen as the instruments of the research in gaining the data. The results from the classroom observation presented that digital storytelling helped students in understanding the material, and it also helped them to write recount text. The result from questionnaire revealed 89% of the students stated that digital storytelling helped them in learning writing recount text. However, 61% of the students stated that bad internet connection hindered the process of producing stage. Therefore, the use of digital storytelling was beneficial for the junior high school students, it helped students to understand the material easily and helped the students to write recount text.